Decision Support System for Web-Based Employee Candidates at PT.Indomarco Prismatama Using the ELECTRE Method - Raudhatul Hasanah Sinaga; Murni Marbun (Institute of Computer Science (IOCS), 2020)
Indomaret or PT.Indomarco Prismatama is one of the largest franchised minimarket companies in Indonesia which is engaged in services and sales. Indomaret is a subsidiary of the Salim Group. The number of Indomaret Stores continues to grow, so PT.Indomarco Prismatama will need a lot of employees so PT.Indomarco has opened job vacancies to meet the specified number of employees. In recruiting prospective employees, Indomaret takes a long time to recruit prospective employees because they have to make decisions fairly and appropriately. The purpose of this study is to design and build a decision support system for recruitment of prospective employees. This system is designed using UML and is built with the programming languages ​​PHP, HTML, CSS, Javascript and MySql as the database. Then determine the prospective employees who successfully passed the selection of employee admissions at PT.Indomarco Prismatama using the ELECTRE method. The ELECTRE (Elimination and Choice Expressing Reality) method is one of the methods of ranking concept decision making, namely by using pairwise comparisons between alternatives on the appropriate criteria. The research result obtained is the decision to determine the applicants who successfully passed the selection. Of the 5 samples of potential applicants, namely A1, A2, A3, A4 and A5 the applicants who successfully passed were A5 because they had the highest score compared to the other samples.